A Research on the Cooperation Models of Higher Education between Pakistan and China under the Belt and Road Initiative - Guoliang, Zhang (Pacific International Journal, 2024)
This study focuses on Pakistan-China higher education cooperation within the Belt and Road Initiative. It examines current cooperation forms like student exchanges, joint programs, and faculty collaborations. Analyzes challenges such as cultural disparities and system differences. Proposes strategies including policy coordination and cultural promotion. Aims to offer insights for enhancing this cooperation, strengthening educational ties, and facilitating broader cultural and economic exchanges between the two nations.